UNDERSTANDING THE INFLUENCE OF LEADERSHIP STYLES ON JOB SATISFACTION: A STUDY IN THE FOOD SERVICE SECTOR IN YOGYAKARTA - Daniel Yudistya Wardhana; Fernando Bagas Yovilianto (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The title of this research is Understanding the Influence of Leadership Styles on Job Satisfaction: A Study in the Food Service Sector in Yogyakarta. This study aims to examine the influence of transformational and transactional leadership on employee job satisfaction in food service providers in Yogyakarta. The research adopts a quantitative approach using primary data collected through an online questionnaire distributed to operational employees. A total of 45 respondents were selected using purposive sampling based on specific criteria relevant to the research objectives. The research instrument employed a five-point Likert scale to measure respondents’ perceptions of leadership styles and job satisfaction. The collected data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that both transformational and transactional leadership have a positive and significant effect on employee job satisfaction. These findings suggest that the implementation of appropriate leadership styles can enhance employee satisfaction and contribute to a more positive and productive work environment within the food service industry.